Dual Biologic Therapy in Moderate to Severe Pediatric Inflammatory Bowel Disease: A Retrospective Study - Magdalena Wlazło; Monika Meglicka; Anna Wiernicka; Marcin Osiecki; Jarosław Kierkuś (MDPI AG, 2022)
Background: Inflammatory bowel diseases in children are characterized by a wide variety of symptoms and often a severe clinical course. In the treatment, we aimed to induce and maintain remission. We focused on assessing the efficacy and safety of the concomitant use of two biologic therapies including: anti-TNF (infliximab, adalimumab) vedolizumab and ustekinumab in a refractory pediatric IBD cohort. Methods: Fourteen children (nine ulcerative colitis, one ulcerative colitis/IBD-unspecified, four Crohn's disease) with a disease duration of 5.2 (8 months-14 years) years, initiated dual therapy at an age of 11.7 (3-17) years after failure of monotherapy with a biological drug. Five patients (36%) were treated with vedolizumab/adalimumab (VDZ + ADA), five (36%) with ustekinumab/adalimumab (UST + ADA), and three (21%) with infliximab/vedolizumab (IFX + VDZ). One patient (7%) was switched from a combination of vedolizumab and adalimumab to ustekinumab and adalimumab during follow-up. Results: A clinical improvement was obtained in ten children (73%; 5 UC, 1 UC/IBD-unspecified, 4 CD) on the PCDAI/PUCAI scale after 4 months of a second biological drug being added. The median fecal calprotectin decreased from 1610 µg/g (140-10,100) to 586 µg/g (5-3410; p = 0.028) between baseline and 4 months. Conclusions: Our clinical experience suggests that dual therapy may be an option for pediatric patients with moderate and severe courses of IBD with limited therapeutic options